A De Novo Arisen Case of Primary Adrenal Insufficiency in an Adolescent Patient With Crohn Disease. Issue 23 (June 2015) - Qiu, Yun; Mao, Ren; Chen, Min-hu; Guidi., Luisa
<x xml:space="preserve">Abstract</x> Abstract Several recent population-based studies have demonstrated that patients with inflammatory bowel disease are likely to have other autoimmune diseases. Here we describe the first de novo arisen case of primary adrenal insufficiency in an adolescent female patient with Crohn disease (CD). A 17-year-old female diagnosed with stricturing colonic CD received the maintenance regimen of Remicade (infliximab) 5 mg/kg every 8 weeks following the standard induction regimen. She had an ileocecostomy due to acute small bowel obstruction at 1.5-year since the last infusion of Remicade. She was presented with skin hyperpigmentation of her face, neck, upper limbs, buccal mucosa and lips, which worsened when commenced on 6-mercaptopurine treatment for prophylaxis of postoperative recurrence. An increased adrenocorticotropic hormone (20.3 pmol/L, range 2–11) measurement was obtained. Radiography of the sella turcica region showed no signs of pituitary disease, or abnormality of bilateral adrenal cortex. Since serum aldosterone was below the reference range, more importantly, assessments for both antiadrenal antibodies and anti-21-hydroxylase antibodies were positive, she was then diagnosed as primary adrenal insufficiency. The symptoms improved after supplement of hydrocortisone. This case highlights a rare immune-mediated comorbidity in an adolescent patient with CD. Recognition of a new pattern of autoimmune endocrine comorbidity enables clinicians to be alert about the possibility of concurrence of primary adrenal insufficiency with CD.